Peran Turnover Intention dalam Memediasi Pengaruh Locus Of Control Terhadap Perilaku Disfungsional Auditor - Ningsih, Ni Wayan Utari; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2018)
An auditor carrying out his profession must be able to avoid the occurrence of dysfunctional behavior by paying attention to the factors that influence it. The research objective is to determine the role of turnover intention in mediating the influence of locus of control on dysfunctional auditor behavior in PT Bank Sinar Mas with a total of 40 auditors as samples through saturated sample methods. Based on the results of the analysis, locus of control variables have a positive and significant effect on auditor dysfunctional behavior. Locus of control has a positive and significant effect on turnover intention. Turnover intention has a positive and significant effect on auditor dysfunctional behavior. Turnover intention mediates the positive influence of locus of control on auditor dysfunctional behavior. Keywords : locus of control, turnover intention, dysfunctional audit behavior